1997
DOI: 10.1111/j.1365-2958.1997.mmi522.x
|View full text |Cite
|
Sign up to set email alerts
|

A peptidoglycan hydrolase similar to bacteriophage endolysins acts as an autolysin in Neisseria gonorrhoeae

Abstract: SummaryWe have identified a gene encoding an autolysin (atlA) from Neisseria gonorrhoeae. The deduced amino acid sequence of AtlA shows significant similarity to the peptidoglycan degrading transglycosylases (endolysins) of bacteriophages lambda and P2, suggesting that the encoded protein also functions in peptidoglycan hydrolysis. An atlA mutant was identical to the wild-type strain in exponential growth rate, but demonstrated reduced lysis and peptidoglycan turnover in the stationary phase of growth. When tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 39 publications
2
39
0
Order By: Relevance
“…The viable counts decreased slowly, and at 50 h more than 10 5 CFU/ml survived. This phenotype is highly similar to that of an atlA mutant of N. gonorrhoeae MS11A (4).…”
supporting
confidence: 57%
“…The viable counts decreased slowly, and at 50 h more than 10 5 CFU/ml survived. This phenotype is highly similar to that of an atlA mutant of N. gonorrhoeae MS11A (4).…”
supporting
confidence: 57%
“…AtlA shows significant similarity to lambda R, the endolysin that breaks open E. coli during the lytic stage of lambda infection (6,14). This similarity suggested that AtlA might also be able to lyse bacterial cells.…”
Section: Resultsmentioning
confidence: 87%
“…The original studies with AtlA suggested that it might be an autolysin (14), but later studies identified a requirement of AtlA for DNA release during the growth phase. atlA insertion mutants had the same phenotype as other T4SS mutants, failing to donate DNA during coculture transformation and showing reduced release of DNA during growth (15,20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations